Sodium manganate-based composite positive electrode material and preparation method and application thereof
By combining sodium-containing compounds, metal oxides and carbon-based materials with sodium manganate to form a composite positive electrode material, the problems of low charge and discharge efficiency, low conductivity and Mn element dissolution of sodium manganate materials are solved, and higher battery performance is achieved.
Patent Information
- Application Number
- CN202411810225.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
AI Technical Summary
Sodium manganate materials have problems such as low first charge and discharge efficiency, low conductivity and Mn element dissolution, and it is difficult to simultaneously improve the charge and discharge efficiency and conductivity through existing modification methods to inhibit the dissolution of Mn element.
By combining sodium-containing compounds, metal oxides and carbon-based materials with sodium manganate, a composite positive electrode material is formed, and the migration rate of sodium ions is increased by the coating of carbon-based materials, and a stable solid solution is formed with sodium manganate and sodium-containing compounds and metal oxides, thereby inhibiting the dissolution of Mn elements.
The first charge and discharge efficiency and conductivity of sodium manganate composite materials are improved, the dissolution of Mn elements is inhibited, and the comprehensive electrochemical performance of the battery is improved.
Smart Images

Figure CN119650638A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of positive electrode materials for sodium ion batteries, and in particular to a preparation method and application of a sodium manganate-based composite positive electrode material. Background Art
[0002] Lithium-ion batteries are limited by the reserves of lithium resources and cannot support the development of both electric vehicles and large-scale energy storage at the same time. Therefore, new energy storage battery technologies must be developed to support their sustainable development. In recent years, sodium-ion batteries have attracted widespread attention due to their advantages such as abundant sodium resources, low cost and good comprehensive performance. Sodium-ion batteries can meet the requirements of low cost, long life and high safety performance in the field of new energy. They can alleviate the problem of limited development of energy storage batteries caused by the shortage of lithium resources to a certain extent and are a beneficial supplement to lithium-ion batteries.
[0003] Layered sodium manganate (Na x MnO2) material contains only two elements, sodium and manganese, and has a very low price advantage and a very broad application prospect. However, the material has disadvantages such as low initial charge and discharge efficiency, low electrical conductivity, and Mn element dissolution, which cause great difficulties for the application of the material.
[0004] In the prior art, in order to solve the problem that the initial charge and discharge efficiency of sodium manganate is low, resulting in low gram capacity and specific energy, the main method is to add sodium supplement materials during battery manufacturing, such as positive electrode sodium supplement, negative electrode sodium supplement and electrolyte sodium supplement; wherein, positive electrode sodium supplement is to add sodium supplement agent during positive electrode pulping during battery manufacturing, which is just to simply mix the sodium supplement agent, positive electrode main material, conductive agent and binder. This method not only prolongs the process time of positive electrode pulping, reduces efficiency and thus increases cost, but also has low intrinsic conductivity and uneven particle size of the sodium supplement agent, and the Na ion escapes and migrates over a long distance, resulting in Na + It cannot be completely removed, thus failing to achieve the expected sodium supplementation effect; and to address the problems of Mn dissolution and low electrical conductivity in sodium manganate materials, metal doping and carbon doping and coating are performed in the materials respectively.
[0005] However, none of these modification methods can achieve the expected results, and it is impossible to simultaneously meet the requirements of improving the initial charge and discharge efficiency and conductivity, and inhibiting the dissolution of the Mn element by only one modification method. Summary of the invention
[0006] The present invention aims to solve the problems existing in the prior art and provide a method for preparing a sodium manganate-based composite positive electrode material. The method improves the initial charge and discharge efficiency and the electrical conductivity, and inhibits the dissolution of the Mn element by compounding a sodium-containing compound, a metal oxide and a carbon-based material with the sodium manganate, thereby optimizing the performance of the sodium manganate composite material.
[0007] According to a first aspect of the present invention, there is provided a sodium manganate-based composite positive electrode material, the positive electrode material comprising sodium manganate, wherein the sodium manganate is doped with a sodium-containing compound, a metal oxide and a carbon-based material;
[0008] Among them, sodium manganate, sodium-containing compounds and metal oxides are all coated with carbon-based materials. The coating of carbon-based materials increases the migration rate of sodium ions in the positive electrode material, and at the same time, sodium manganate forms a stable solid solution with the sodium-containing compound and the metal oxide, respectively, thereby inhibiting the dissolution of manganese in sodium manganate.
[0009] As an optional embodiment, the sodium manganate includes Na x MO2, x is the molar ratio, and its value is 0<x≤0.67.
[0010] As an optional embodiment, based on the total mass of the sodium manganate-based composite positive electrode material, the mass proportion of sodium manganate is 82% to 97.8%, the mass proportion of the sodium-containing compound is 1% to 10%, the mass proportion of the metal oxide is 0.2% to 3%, and the mass proportion of the carbon-based material is 1% to 5%.
[0011] As an optional embodiment, the sodium-containing compound includes NaF, NaS, Na3N, Na3P, Na2NiO2, Na2Ni 0.5 Mn 0.5 One or more of O2, Na5FeO4, Na5FeO8, and Na8FeO4.
[0012] As an optional embodiment, the metal oxide includes one or more of Al2O3, MgO, SiO2, TiO2, ZrO2, Ga2O3, V2O5, Co3O4, ZnO, SnO, MoO3, Nb2O5, NiO, Ta2O5, and Gd2O3.
[0013] As an optional embodiment, the carbon-based material includes one or more of conductive carbon black SP, conductive carbon black C60, conductive graphite Ks-6, conductive graphite Ks-15, carbon nanotubes, graphene, VGCF, and Ketjen black.
[0014] According to a second aspect of the present invention, there is provided a method for preparing the aforementioned sodium manganate-based composite positive electrode material, comprising the following steps:
[0015] After uniformly mixing the sodium source, the manganese source, the first solvent, the first complexing agent and the first dispersant, reacting at a desired temperature to obtain a first solution;
[0016] The sodium-containing compound, the second solvent, the second complexing agent and the second dispersant are reacted at a desired temperature to obtain a second solution; the metal oxide, the third solvent, the third complexing agent and the third dispersant are reacted at a desired temperature to obtain a third solution;
[0017] reacting the carbon-based material, the fourth solvent and the fourth dispersant at a desired temperature to obtain a fourth solution;
[0018] The second solution, the third solution and the fourth solution are slowly added to the first solution in sequence, reacted at a desired temperature to obtain a fifth solution, and the fifth solution is evaporated to remove the solvent to obtain a dry gel, and the dry gel is ground to obtain a gel powder;
[0019] The gel powder is pre-sintered under the protection of an inert gas to remove easily decomposed products in the gel powder, and then sintered at a desired temperature to obtain the sodium manganate-based composite positive electrode material.
[0020] As an optional embodiment, the sodium source includes one or more of sodium carbonate, sodium bicarbonate, hydroxide, sodium formate, sodium acetate, and sodium propionate, and the manganese source includes one or more of manganese dioxide, manganese sulfate, manganese nitrate, manganese chloride, and manganese acetate.
[0021] As an optional embodiment, the molar ratio of the sodium source to the manganese source is (0.66-0.69):1; the mass ratio of the sodium source to the manganese source, the first solvent, the first complexing agent, and the first dispersant is 1:(1-2):(0.02-0.05):(0.005-0.02);
[0022] The mass ratio of the sodium-containing compound, the second solvent, the second complexing agent, and the second dispersant is 1:(5-15):(0.2-0.8):(0.1-0.5);
[0023] The mass ratio of the metal oxide, the third solvent, the third complexing agent, and the third dispersant is 1:(5-15):(0.2-0.8):(0.1-0.5);
[0024] The mass ratio of the carbon-based material, the fourth solvent, and the fourth dispersant is 1:(5-15):(0.2-0.8):(0.1-0.5).
[0025] As an optional implementation, the gel powder is pre-fired under inert gas protection at a temperature of 300°C to 500°C for 1 hour to 8 hours; the sintering temperature is 600°C to 900°C for 10 hours to 24 hours.
[0026] According to a third aspect of the present invention, there is provided a use of the aforementioned sodium manganate-based composite positive electrode material in a sodium ion battery.
[0027] It can be seen from the above technical solutions of the present invention that the sodium manganate-based composite positive electrode material proposed in the present invention is composited with sodium manganate using sodium supplementing materials, metal oxides and carbon-based materials. The carbon-based material can not only coat the sodium manganate material, but also coat the sodium-containing compound and the metal oxide, thereby helping the sodium-containing compound and the metal oxide to form a stable solid solution with the sodium manganate, inhibiting the distortion of the Mn lattice and better inhibiting the dissolution of Mn in the sodium manganate; at the same time, the carbon coating can improve the conductivity of the sodium manganate, the sodium-containing compound and the metal oxide, thereby making the Na + The migration rate in the material is increased, making Na + Faster and better deintercalation in the material achieves better sodium supplementation effect; in addition, the carbon coating also isolates the sodium manganate material from direct contact with the electrolyte, thereby further inhibiting the dissolution of Mn, and the carbon material can also occupy the lattice defects of Mn to form a stable solid solution, inhibiting the distortion of the Mn lattice;
[0028] In this way, by compounding sodium supplement materials, metal oxides and carbon-based materials with sodium manganate, the initial charge and discharge efficiency and conductivity are improved, and the dissolution of the Mn element is inhibited, thereby improving the comprehensive electrochemical performance of the corresponding battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 is an XRD pattern of a sample in an example of the present invention.
[0030] Figure 2 2a is a sample of Comparative Example 1, 2b is a sample of Comparative Example 2, 2c is a sample of Comparative Example 3, and 2d is a sample of Example 1.
[0031] Figure 3 : is the charge and discharge curve of the sample in the example of the present invention. DETAILED DESCRIPTION
[0032] In order to better understand the technical content of the present invention, specific embodiments are given and described as follows in conjunction with the accompanying drawings.
[0033] Various aspects of the present invention are described in this disclosure with reference to the accompanying drawings, in which many illustrative embodiments are shown. The embodiments of the present disclosure are not necessarily intended to include all aspects of the present invention. It should be understood that the various concepts and embodiments introduced above, as well as those described in more detail below, can be implemented in any of many ways.
[0034] In order to solve the problem of low initial charge and discharge efficiency of sodium manganate, which leads to low gram capacity and specific energy, in addition to the positive electrode sodium replenishment method in existing materials, there are also negative electrode sodium replenishment and electrolyte sodium replenishment; negative electrode sodium replenishment is to coat the negative electrode material with metallic sodium or organic matter of metallic sodium, which causes environmental pollution and the hazard of metallic sodium explosion, and also increases the cost of materials, equipment and environment; electrolyte sodium replenishment is to add sodium replenisher to the electrolyte, and there are the problems of immiscibility of the sodium replenisher and the electrolyte and side reactions causing the performance of the electrolyte to deteriorate.
[0035] The present invention aims to provide a sodium manganate-based composite positive electrode material, which comprehensively improves the problems of low initial charge and discharge efficiency, low electrical conductivity, and Mn element dissolution in sodium manganate-based positive electrode materials.
[0036] Sodium manganate based composite cathode material
[0037] In an exemplary embodiment of the present invention, a sodium manganate-based composite positive electrode material is provided, the positive electrode material comprising sodium manganate, wherein the sodium manganate is doped with a sodium-containing compound, a metal oxide and a carbon-based material;
[0038] Among them, sodium manganate, sodium-containing compounds and metal oxides are all coated with carbon-based materials. The coating of carbon-based materials increases the migration rate of sodium ions in the positive electrode material, and at the same time, sodium manganate forms a stable solid solution with the sodium-containing compound and the metal oxide, respectively, thereby inhibiting the dissolution of manganese in sodium manganate.
[0039] As an optional example, sodium manganate includes Na x MO2, x is the molar ratio, and its value is 0<x≤0.67.
[0040] As an optional example, based on the total mass of the sodium manganate-based composite positive electrode material, the mass proportion of sodium manganate is 82% to 97.8%, the mass proportion of the sodium-containing compound is 1% to 10%, the mass proportion of the metal oxide is 0.2% to 3%, and the mass proportion of the carbon-based material is 1% to 5%.
[0041] As optional examples, sodium-containing compounds include NaF, NaS, Na3N, Na3P, Na2NiO2, Na2Ni 0.5 Mn 0.5 One or more of O2, Na5FeO4, Na5FeO8, and Na8FeO4.
[0042] As optional examples, the metal oxide includes one or more of Al2O3, MgO, SiO2, TiO2, ZrO2, Ga2O3, V2O5, Co3O4, ZnO, SnO, MoO3, Nb2O5, NiO, Ta2O5, and Gd2O3.
[0043] As an optional example, the carbon-based material includes one or more of conductive carbon black SP, conductive carbon black C60, conductive graphite Ks-6, conductive graphite Ks-15, carbon nanotubes, graphene, VGCF, and Ketjen black.
[0044] Preparation method
[0045] The preparation method of the sodium manganate-based composite positive electrode material of the invention comprises the following steps: uniformly mixing a sodium source, a manganese source, a solvent, a dispersant and a complexing agent to obtain a sodium manganate solution; then adding the obtained sodium-containing compound solution, a metal oxide solution and a carbon conductive agent solution to the sodium manganate solution to obtain a composite material solution; and finally evaporating and sintering the solution to obtain the sodium manganate composite sodium ion battery positive electrode material.
[0046] The method for preparing an exemplary sodium manganate-based composite positive electrode material of the present invention comprises the following steps:
[0047] After uniformly mixing the sodium source, the manganese source, the first solvent, the first complexing agent and the first dispersant, reacting at 40° C. to 120° C. for 30 min to 150 min to obtain a first solution;
[0048] reacting the sodium-containing compound, the second solvent, the second complexing agent and the second dispersant at 30° C. to 60° C. for 30 min to 90 min to obtain a second solution;
[0049] reacting the metal oxide, the third solvent, the third complexing agent and the third dispersant at 30° C. to 60° C. for 30 min to 90 min to obtain a third solution;
[0050] The carbon-based material, the fourth solvent and the fourth dispersant are reacted at 30° C. to 60° C. for 30 min to 90 min to obtain a fourth solution.
[0051] The second solution, the third solution and the fourth solution are slowly added to the first solution in sequence, and the mixture is reacted at 40°C to 90°C for 60min to 120min to obtain a fifth solution, and the fifth solution is evaporated at 80°C to 150°C to remove the solvent to obtain a dry gel, and the dry gel is ground and crushed to obtain a gel powder.
[0052] The gel powder is pre-calcined at 300°C to 500°C for 1h to 8h under inert gas protection to remove easily decomposed products in the gel powder, and then sintered at 600°C to 900°C for 10h to 24h to obtain a sodium manganate-based composite positive electrode material.
[0053] As optional examples, the sodium source includes one or more of sodium carbonate, sodium bicarbonate, hydroxide, sodium formate, sodium acetate, and sodium propionate, and the manganese source includes one or more of manganese dioxide, manganese sulfate, manganese nitrate, manganese chloride, and manganese acetate.
[0054] It can be understood that the first solvent, the first complexing agent and the first dispersing agent can be substances commonly used in the art.
[0055] In an optional example, the first solvent includes one or more of deionized water, ethanol, ethylene glycol, acetone, N, N-dimethylpyrrolidone (NMP); the first complexing agent includes at least one of C3-C20 carboxylic acids or poly-C3-C20 carboxylic acids, particularly preferably at least one of citric acid, polyacrylic acid or myristic acid; the first dispersant includes one or both of CMC and PV.
[0056] In an optional example, the second solvent includes one or more of deionized water, ethanol, ethylene glycol, acetone, N, N-dimethylpyrrolidone (NMP); the second complexing agent includes at least one of C3-C20 carboxylic acids or poly-C3-C20 carboxylic acids, particularly preferably at least one of citric acid, polyacrylic acid or myristic acid; the second dispersant includes one or both of CMC and PV.
[0057] In an optional example, the third solvent includes one or more of deionized water, ethanol, ethylene glycol, acetone, N, N-dimethylpyrrolidone (NMP); the third complexing agent includes at least one of C3-C20 carboxylic acids or poly-C3-C20 carboxylic acids, particularly preferably at least one of citric acid, polyacrylic acid or myristic acid; the third dispersant includes one or both of CMC and PV.
[0058] In an optional example, the fourth solvent includes one or more of deionized water, ethanol, ethylene glycol, acetone, and N,N-dimethylpyrrolidone (NMP); and the fourth dispersant includes one or two of CMC and PV.
[0059] As an optional example, the molar ratio of the sodium source to the manganese source is (0.66-0.69):1; the mass ratio of the sodium source to the manganese source, the first solvent, the first complexing agent, and the first dispersant is 1:(1-2):(0.02-0.05):(0.005-0.02);
[0060] The mass ratio of the sodium-containing compound, the second solvent, the second complexing agent, and the second dispersant is 1:(5-15):(0.2-0.8):(0.1-0.5);
[0061] The mass ratio of the metal oxide, the third solvent, the third complexing agent, and the third dispersant is 1:(5-15):(0.2-0.8):(0.1-0.5);
[0062] The mass ratio of the carbon-based material, the fourth solvent, and the fourth dispersant is 1:(5-15):(0.2-0.8):(0.1-0.5).
[0063] As an optional example, the inert gas includes one of nitrogen, argon, carbon dioxide, or a mixture of the two or more.
[0064] Application of sodium manganate-based composite cathode materials in sodium ion batteries
[0065] In other exemplary embodiments of the present invention, there is also provided a use of the aforementioned sodium manganate-based composite positive electrode material in a sodium ion battery.
[0066] The present invention also provides a sodium ion battery, which adopts the above-mentioned sodium manganate-based composite positive electrode material and is obtained through sodium ion battery manufacturing processes such as coating, rolling, slitting, assembling, liquid injection, formation, and capacity division.
[0067] In an optional example, the preparation of the aforementioned sodium ion battery includes:
[0068] The prepared sodium manganate-based composite positive electrode material is evenly mixed with a conductive agent, a binder, and a solvent to obtain a positive electrode slurry, and the positive electrode slurry is coated on a foil to obtain a positive electrode sheet.
[0069] The negative electrode main material, conductive agent, binder and solvent are mixed evenly to obtain negative electrode slurry, and the negative electrode slurry is evenly coated on the foil to obtain a negative electrode sheet.
[0070] The positive electrode sheet and the negative electrode sheet are subjected to sodium ion manufacturing processes such as rolling, slitting, winding, assembling, baking, liquid injection, sealing, formation, and capacity division to obtain a sodium ion battery.
[0071] in,
[0072] The positive electrode conductive agent includes one or more of SP, KS-6, KS-16, C60, VGCF, and CNTs slurry.
[0073] The positive electrode solvent includes one or more of NMP and deionized water.
[0074] The negative electrode main material includes one or more of hard carbon, soft carbon, MoS, SnO2, and titanium-based compounds.
[0075] The negative electrode conductive agent includes one or more of SP, KS-6, KS-16, C60, VGCF, and CNTs slurry.
[0076] The negative electrode binder includes one or more of oily or water-based binders such as PVDF, PTFE, SBR, CMC, and PAA.
[0077] The negative electrode solvent includes NMP or water.
[0078] The diaphragms include PP, PE, PP / PE / PP, polyimide or acrylic diaphragms.
[0079] The core consists of a stack or a roll.
[0080] Sodium-ion battery forms include soft pack, cylindrical, aluminum shell or special shape.
[0081] The sodium ion battery prepared by using the sodium manganate-based composite positive electrode material of the present invention can improve the initial charge and discharge efficiency, gram capacity and specific energy of the sodium ion battery, and can also avoid the appearance of impurities and the dissolution of the Mn element, thereby improving the cycle and rate performance of the battery.
[0082] For better understanding, the present invention is further described below in conjunction with several specific examples, but the preparation process is not limited thereto, and the content of the present invention is not limited thereto.
[0083] Unless otherwise specified, the materials in the examples were prepared according to existing methods or directly purchased from the market.
[0084] Example 1
[0085] Step A), 91 parts of sodium acetate, 268 parts of manganese acetate, 500 parts of ethylene glycol solvent, 10 parts of citric acid complexing agent, and 3 parts of CMC dispersant are first mixed uniformly, and then heated to 80° C. and reacted for 90 minutes to obtain a sodium manganate solution 1.
[0086] 5 parts of Na2Ni 0.5 Mn 0.5 O2 sodium-containing compound, 50 parts of ethylene glycol solution, 1 part of dispersant CMC, and 3 parts of complexing agent polyacrylic acid are mixed at 50°C for 30 minutes to obtain a uniform sodium-containing compound solution 2.
[0087] 1 part of TiO2, 10 parts of ethylene glycol solution, 0.2 parts of dispersant CMC, and 0.6 parts of complexing agent polyacrylic acid were mixed at 50°C for 30 minutes to obtain a uniform TiO2 solution 3.
[0088] 3 parts of Ketjen black, 30 parts of solvent NMP, and 0.6 parts of dispersant PVP were mixed at 50° C. for 30 minutes to obtain a Ketjen black conductive solution 4.
[0089] Step B), solution 2, solution 3 and solution 4 are slowly added dropwise to solution 1 in sequence, and then the two solutions are mixed at 60°C for 30 minutes to obtain a uniform sodium manganate / Na2Ni 0.5 Mn 0.5 O2 / TiO2 / Ketjen black mixed solution, then evaporate the solution at 110℃ to remove the volatile components to obtain sodium manganate / Na2Ni 0.5 Mn 0.5 The dry gel of O2 / TiO2 / Ketjen black is ground to obtain a powder.
[0090] Step C), the powder was heated to 450°C for 4 hours under argon gas to decompose and remove the volatile components in the powder, and then heated to 850°C for 16 hours to finally obtain 95% Na 0.67 MnO2 / 3%Na2Ni 0.5 Mn 0.5 O2 / 0.5%TiO2 / 1.5% Ketjen black composite sodium ion positive electrode material.
[0091] Example 2
[0092] Step A), 91 parts of sodium acetate, 268 parts of manganese acetate, 500 parts of ethylene glycol solvent, 10 parts of citric acid complexing agent, and 3 parts of CMC dispersant are first mixed uniformly, and then heated to 80° C. and reacted for 90 minutes to obtain a sodium manganate solution 1.
[0093] 5 parts of NaF sodium-containing compound, 50 parts of ethylene glycol solution, 1 part of dispersant CMC, and 3 parts of complexing agent polyacrylic acid were mixed at 50° C. for 30 minutes to obtain a uniform sodium-containing compound solution 2.
[0094] 1 part of MgO, 10 parts of ethylene glycol solution, 0.2 parts of dispersant CMC, and 0.6 parts of complexing agent polyacrylic acid were mixed at 50° C. for 30 minutes to obtain a uniform MgO solution 3.
[0095] 3 parts of Ketjen black, 30 parts of solvent NMP, and 0.6 parts of dispersant PVP were mixed at 50° C. for 30 minutes to obtain a Ketjen black conductive solution 4.
[0096] Step B), solution 2, solution 3 and solution 4 are slowly added dropwise to solution 1 in sequence, and then the two solutions are mixed at 60° C. for 30 minutes to obtain a uniform sodium manganate / NaF / MgO / Ketjen black mixed solution, and then the solution is evaporated at 110° C. to remove volatile components to obtain a sodium manganate / NaF / MgO / Ketjen black dry gel, which is ground to obtain a powder.
[0097] Step C) The powder was pre-calcined at 450°C for 4 hours under argon gas to decompose and remove the volatile components in the powder, and then the temperature was raised to 850°C and sintered for 16 hours to finally obtain 95% Na 0.67 MnO2 / 3%NaF / 0.5%MgO / 1.5%Ketjen black composite sodium ion positive electrode material.
[0098] Example 3
[0099] Step A), 91 parts of sodium acetate, 268 parts of manganese acetate, 500 parts of ethylene glycol solvent, 10 parts of citric acid complexing agent, and 3 parts of CMC dispersant are first mixed uniformly, and then heated to 80° C. and reacted for 90 minutes to obtain a sodium manganate solution 1.
[0100] 5 parts of Na8FeO4, 50 parts of diethanol solution, 1 part of dispersant CMC, and 3 parts of complexing agent polyacrylic acid were mixed at 50°C for 30 minutes to obtain a uniform sodium compound solution 2.
[0101] 1 part of Al2O3, 10 parts of ethylene glycol solution, 0.2 parts of dispersant CMC, and 0.6 parts of complexing agent polyacrylic acid were mixed at 50°C for 30 minutes to obtain a uniform Al2O3 solution 3.
[0102] 3 parts of Ketjen black, 30 parts of solvent NMP, and 0.6 parts of dispersant PVP were mixed at 50° C. for 30 minutes to obtain a Ketjen black conductive solution 4.
[0103] Step B), solution 2, solution 3 and solution 4 are slowly added dropwise to solution 1 in sequence, and then the two solutions are mixed at 60° C. for 30 minutes to obtain a uniform sodium manganate / Na8FeO4 / Al2O3 / Ketjen black mixed solution, and then the solution is evaporated at 110° C. to remove volatile components to obtain a sodium manganate / Na8FeO4 / Al2O3 / Ketjen black dry gel, which is ground to obtain a powder.
[0104] Step C), the powder was heated to 450°C for 4 hours under argon gas to decompose and remove the volatile components in the powder, and then heated to 850°C for 16 hours to finally obtain 95% Na 0.67 MnO2 / 3%Na8FeO4 / 0.5%Al2O3 / 1.5%Ketjen black composite sodium ion positive electrode material.
[0105] Example 4
[0106] Step A), 91 parts of sodium acetate, 268 parts of manganese acetate, 500 parts of ethylene glycol solvent, 10 parts of citric acid complexing agent, and 3 parts of CMC dispersant are first mixed uniformly, and then heated to 80° C. and reacted for 90 minutes to obtain a sodium manganate solution 1.
[0107] 15 parts of Na8FeO4, 150 parts of diethanol solution, 3 parts of dispersant CMC, and 9 parts of complexing agent polyacrylic acid were mixed at 50°C for 30 minutes to obtain a uniform sodium compound solution 2.
[0108] 6 parts of Al2O3, 60 parts of ethylene glycol solution, 1 part of dispersant CMC, and 3.5 parts of complexing agent polyacrylic acid were mixed at 50°C for 30 minutes to obtain a uniform Al2O3 solution 3.
[0109] 10 parts of Ketjen black, 100 parts of solvent NMP, and 2 parts of dispersant PVP were mixed at 50° C. for 30 minutes to obtain a Ketjen black conductive solution 4.
[0110] Step B), solution 2, solution 3 and solution 4 are slowly added dropwise to solution 1 in sequence, and then the two solutions are mixed at 60° C. for 30 minutes to obtain a uniform sodium manganate / Na8FeO4 / Al2O3 / Ketjen black mixed solution, and then the solution is evaporated at 110° C. to remove volatile components to obtain a sodium manganate / Na8FeO4 / Al2O3 / Ketjen black dry gel, which is ground to obtain a powder.
[0111] Step C), the powder was heated to 450°C for 4 hours under argon gas to decompose and remove the volatile components in the powder, and then heated to 850°C for 16 hours to finally obtain 82% Na 0.67 MnO2 / 10%Na8FeO4 / 3%Al2O3 / 5%Ketjen black composite sodium ion positive electrode material.
[0112] Comparative Example 1
[0113] [Preparation of positive electrode material of sodium manganate]
[0114] Step A), 91 parts of sodium acetate, 268 parts of manganese acetate, 500 parts of ethylene glycol solvent, 10 parts of citric acid complexing agent, and 3 parts of CMC dispersant are first mixed uniformly, and then heated to 80° C. and reacted for 90 minutes to obtain a sodium manganate solution.
[0115] Step B), evaporating the sodium manganate solution at 110° C. to remove volatile components, obtain a sodium manganate dry gel, and grind to obtain a powder.
[0116] Step C), the powder is heated to 450°C for 4 hours under argon gas to decompose and remove the volatile components in the powder, and then heated to 850°C for 16 hours to finally obtain Na 0.67 MnO2 positive electrode material.
[0117] Comparative Example 2
[0118] [Preparation of positive electrode materials of sodium manganate / sodium-containing compounds]
[0119] Step A), 91 parts of sodium acetate, 268 parts of manganese acetate, 500 parts of ethylene glycol solvent, 10 parts of citric acid complexing agent, and 3 parts of CMC dispersant are first mixed uniformly, and then heated to 80° C. and reacted for 90 minutes to obtain a sodium manganate solution 1.
[0120] 5 parts of Na2Ni 0.5 Mn 0.5 O2 sodium-containing compound, 50 parts of diethanol solution, 1 part of dispersant CMC, and 3 parts of complexing agent polyacrylic acid are mixed at 50°C for 30 minutes to obtain a uniform sodium-containing compound solution 2.
[0121] Step B), slowly add solution 2 to solution 1, and then mix the two solutions at 60°C for 30 minutes to obtain a uniform sodium manganate / Na2Ni 0.5 Mn 0.5 O2 mixed solution, and then evaporate the solution at 110 ° C to remove the volatile components to obtain sodium manganate / Na2Ni 0.5 Mn 0.5 O2 dry gel, grind to obtain powder.
[0122] Step C), the powder was heated to 450°C for 4 hours under argon gas to decompose and remove the volatile components in the powder, and then heated to 850°C for 16 hours to finally obtain 97% Na 0.67 MnO2 / 3%Na2Ni 0.5 Mn 0.5 O2 positive electrode material.
[0123] Comparative Example 3
[0124] [Preparation of positive electrode materials of sodium manganate / sodium-containing compounds / metal oxides]
[0125] Step A), 91 parts of sodium acetate, 268 parts of manganese acetate, 500 parts of ethylene glycol solvent, 10 parts of citric acid complexing agent, and 3 parts of CMC dispersant are first mixed uniformly, and then heated to 80° C. and reacted for 90 minutes to obtain a sodium manganate crystal solution 1.
[0126] 5 parts of Na2Ni 0.5 Mn 0.5 O2 sodium-containing compound, 50 parts of ethylene glycol solution, 1 part of dispersant CMC, and 3 parts of complexing agent polyacrylic acid are mixed at 50°C for 30 minutes to obtain a uniform sodium-containing compound solution 2.
[0127] 1 part of TiO2, 10 parts of ethylene glycol solution, 0.2 parts of dispersant CMC, and 0.6 parts of complexing agent polyacrylic acid were mixed at 50°C for 30 minutes to obtain a uniform TiO2 solution 3.
[0128] Step B), solution 2 and solution 3 are slowly added to solution 1, and then the two solutions are mixed at 60°C for 30 minutes to obtain a uniform sodium manganate / Na2Ni 0.5 Mn 0.5 O2 / TiO2 mixed solution, and then evaporate the solution at 110℃ to remove the volatile components to obtain sodium manganate / Na2Ni 0.5 Mn 0.5 O2 / TiO2 dry gel, grind to obtain powder,
[0129] Step C) The powder was then heated to 450°C for 4 hours under argon gas to decompose and remove the volatile components in the powder, and then heated to 850°C for 16 hours to finally obtain 96.5% Na 0.67 MnO2 / 3%Na2Ni 0.5 Mn 0.5 O2 / 0.5%TiO2 positive electrode material.
[0130] XRD test
[0131] The sample of Example 1 was subjected to XRD test, and the results were as follows: Figure 1 shown.
[0132] The XRD spectrum shows that the material is pure sodium manganate material. Due to the low content of sodium compounds, metal oxides, carbon and other materials, they cannot be shown in the XRD spectrum.
[0133] SEM scanning and EDX spectrum detection
[0134] The samples of Example 1 and Comparative Examples 1-3 were subjected to SEM scanning and EDX spectrum detection, and the results are as follows: Figure 2 And as shown in Table 1.
[0135] Combination Figure 1 As can be seen from Table 1, the Na content of the composite material prepared by the present invention is nearly 2% higher than that of the material without adding the sodium supplement, and the increase is derived from the sodium-containing compound, and the presence of the sodium-containing compound is proved from the increase in the Ni and Na elements; at the same time, the doped Ti and C elements are detected, and the content is consistent with the doping amount.
[0136] Table 1
[0137]
[0138] Combining XRD detection and EDX spectrum detection can prove that the present invention successfully synthesizes the sodium manganate-based composite positive electrode material.
[0139] Electrochemical performance test
[0140] The sodium ion battery preparation method is as follows:
[0141] 1) 95 parts of the prepared positive electrode material, 1 part of SP conductive agent 1, 2 parts of CNTs conductive agent 2, 2 parts of PVDF, and 40 parts of solvent NMP were mixed uniformly at a rate of 150 g / m 2 The surface density is evenly coated on a 12μm thick aluminum foil, and then rolled to roll the pole piece to a thickness of 120μm.
[0142] 2) 95 parts of sodium ion battery negative electrode material hard carbon, 1.5 parts of thickener CMC, 2 parts of conductive agent SP, 2.5 parts of binder SBR, and 95 parts of solvent deionized water were mixed evenly at 70 g / m 2 The surface density is evenly coated on a 12μm thick aluminum foil, and then rolled to roll the pole piece to a thickness of 167μm.
[0143] 3) The rolled positive and negative electrode sheets are cut and wound with a 12 μm thick PE separator, and then put into the shell, rolled groove, spot bottom welding, baked, injected, cap welding, sealed, and then infiltrated, formed, and divided into volumes to obtain a sodium ion battery cylindrical battery.
[0144] According to the above method, sodium ion batteries were prepared using the materials of Examples 1-3 and Comparative Examples 1-3 as positive electrode materials. The electrochemical properties of the positive electrode materials were tested in a test voltage range of 2 to 4.15 V. The results are shown in Table 2.
[0145] Table 2
[0146]
[0147] Combination Figure 3 As can be seen from Table 2, after the sample of Example 1 is coated and doped with Ketjen black carbon, the conductivity of the entire sodium manganate composite material is improved, which not only enables the sodium ions in the sodium supplement material to be quickly deintercalated, but also improves the effect of the metal oxide in inhibiting the dissolution of Mn, so the initial charge and discharge efficiency, gram capacity, cycle and rate are all improved; the sample test results of Examples 2 and 3 prove that other sodium supplement materials and metal oxides also have similar effects.
[0148] The test results of the samples of comparative example 1 show that pure sodium manganate has the problem of poor initial charge and discharge efficiency, gram capacity, rate and cycle; after the samples of comparative example 2 are doped and coated with sodium-containing compounds, not only can the initial charge and discharge efficiency, gram capacity and specific energy of the battery be improved, but the sodium-containing compound can form a solid solution with Mn in sodium manganate, which can inhibit the dissolution of Mn, thereby improving the battery cycle and rate performance; after the samples of comparative example 3 are doped and coated with metal oxides, not only can the dissolution of Mn in sodium manganate be inhibited, but also the conductivity of the material can be improved, thereby further improving the cycle and rate; however, due to the absence of carbon coating, the overall conductivity of the sodium manganate composite material is relatively low, and the sodium-containing compound, the metal oxide and the Mn in the sodium manganate cannot form a stable solid solution, and the carbon-containing coating cannot improve the conductivity of sodium manganate, the sodium-containing compound and the metal oxide, which affects the Na + The migration rate in the material thus affects various properties to a certain extent, and the detection performance of the sample in Example 1 cannot be achieved.
[0149] It can be seen from the above that in the sodium manganate-based composite positive electrode material of the present invention, the three materials of sodium-containing compound, metal oxide and carbon-based material not only exert their respective performance characteristics, but also interact with each other, so that the performance of the sodium manganate composite material is optimized.
[0150] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. A person with ordinary knowledge in the technical field to which the present invention belongs may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the definition of the claims.
Claims
1. A sodium manganate-based composite positive electrode material, characterized in that: The positive electrode material includes sodium manganate, wherein the sodium manganate is doped with a sodium-containing compound, a metal oxide and a carbon-based material; Among them, sodium manganate, sodium-containing compounds and metal oxides are all coated with carbon-based materials. The coating of carbon-based materials increases the migration rate of sodium ions in the positive electrode material, and at the same time, sodium manganate forms a stable solid solution with the sodium-containing compound and the metal oxide, respectively, thereby inhibiting the dissolution of manganese in sodium manganate.
2. The sodium manganate-based composite positive electrode material according to claim 1, characterized in that: The sodium manganate comprises Na x MO2, x is the molar ratio, and its value is 0<x≤0.
67.
3. The sodium manganate-based composite positive electrode material according to claim 1, characterized in that: Based on the total mass of the sodium manganate-based composite positive electrode material, the mass of sodium manganate accounts for 82% to 97.8%, the mass of the sodium-containing compound accounts for 1% to 10%, the mass of the metal oxide accounts for 0.2% to 3%, and the mass of the carbon-based material accounts for 1% to 5%.
4. The sodium manganate-based composite positive electrode material according to claim 1, characterized in that: The sodium-containing compounds include NaF, NaS, Na3N, Na3P, Na2NiO2, Na2Ni 0.5 Mn 0.5 One or more of O2, Na5FeO4, Na5FeO8, and Na8FeO4.
5. The sodium manganate-based composite positive electrode material according to claim 1, characterized in that: The metal oxide includes one or more of Al2O3, MgO, SiO2, TiO2, ZrO2, Ga2O3, V2O5, Co3O4, ZnO, SnO, MoO3, Nb2O5, NiO, Ta2O5, and Gd2O3.
6. The sodium manganate-based composite positive electrode material according to claim 1, characterized in that: The carbon-based material includes one or more of conductive carbon black SP, conductive carbon black C60, conductive graphite Ks-6, conductive graphite Ks-15, carbon nanotubes, graphene, VGCF, and Ketjen black.
7. A method for preparing the sodium manganate-based composite positive electrode material according to any one of claims 1 to 6, characterized in that: The following steps are involved: After uniformly mixing the sodium source, the manganese source, the first solvent, the first complexing agent and the first dispersant, reacting at a desired temperature to obtain a first solution; The sodium-containing compound, the second solvent, the second complexing agent and the second dispersant are reacted at a desired temperature to obtain a second solution; the metal oxide, the third solvent, the third complexing agent and the third dispersant are reacted at a desired temperature to obtain a third solution; reacting the carbon-based material, the fourth solvent and the fourth dispersant at a desired temperature to obtain a fourth solution; The second solution, the third solution and the fourth solution are slowly added to the first solution in sequence, reacted at a desired temperature to obtain a fifth solution, and the fifth solution is evaporated to remove the solvent to obtain a dry gel, and the dry gel is ground to obtain a gel powder; The gel powder is pre-sintered under the protection of an inert gas to remove easily decomposed products in the gel powder, and then sintered at a desired temperature to obtain the sodium manganate-based composite positive electrode material.
8. The preparation method according to claim 7, characterized in that: The sodium source includes one or more of sodium carbonate, sodium bicarbonate, hydroxide, sodium formate, sodium acetate, and sodium propionate; the manganese source includes one or more of manganese dioxide, manganese sulfate, manganese nitrate, manganese chloride, and manganese acetate.
9. The preparation method according to claim 7, characterized in that: The molar ratio of the sodium source to the manganese source is (0.66-0.69):1; the mass ratio of the sodium source to the manganese source, the first solvent, the first complexing agent, and the first dispersant is 1:(1-2):(0.02-0.05):(0.005-0.02); The mass ratio of the sodium-containing compound, the second solvent, the second complexing agent, and the second dispersant is 1:(5-15):(0.2-0.8):(0.1-0.5); The mass ratio of the metal oxide, the third solvent, the third complexing agent, and the third dispersant is 1:(5-15):(0.2-0.8):(0.1-0.5); The mass ratio of the carbon-based material, the fourth solvent, and the fourth dispersant is 1:(5-15):(0.2-0.8):(0.1-0.5).
10. Use of the sodium manganate-based composite positive electrode material according to any one of claims 1 to 6 in a sodium ion battery.